13.9k views
24 votes
How to solve a equation using elemination method

User KentH
by
5.1k points

1 Answer

8 votes

Answer:

Below.

Explanation:

I assume you are referring to a system of equations.

Example:

2x - y = 4

x + y = 5

If we add these 2 equations then the y is eliminated because -y + y = 0:-

3x + 0 = 9

x = 3

Now we plug x = 3 into the first equation to find y:

2(3) - y = 4

-y = 4 - 6 = -2

y = 2.

If we cannot eliminate one of the variables we multiply one of the equations so that one of the variables so that it can be eliminated.

For example:

2x - 3y = 5 A

x + y = 6 B

We multiply the second equation B by 3 so that when we add -3y + 3y gets eliminated:

3x + 3y = 18

- so adding this to equation A

5x + 0 = 23.

In some cases we may have to multiply both equations by different values to get terms that can be eliminated.

User Se
by
4.1k points